Kinetic studies of ICF implosions. (May 2016) - Kagan, Grigory; Herrmann, H. W.; Kim, Y.-H.; Schmitt, M. J.; Hakel, P.; Hsu, S. C.; Hoffman, N. M.; Svyatsky, D.; Baalrud, S. D.; Daligault, J. O.; Sio, H.; Zylstra, A. B.; et al.
Abstract: Kinetic effects on inertial confinement fusion have been investigated. In particular, inter-ion-species diffusion and suprathermal ion distribution have been analyzed. The former drives separation of the fuel constituents in the hot reacting core and governs mix at the shell/fuel interface. The latter underlie measurements obtained with nuclear diagnostics, including the fusion yield and inferred ion burn temperatures. Basic mechanisms behind and practical consequences from these effects are discussed.